AltWOA: Altruistic Whale Optimization Algorithm for feature selection on microarray datasets - Kundu, Rohit; Chattopadhyay, Soham; Cuevas, Erik; Sarkar, Ram (Computers in biology and medicine, 2022)
The data-driven modern era has enabled the collection of large amounts of biomedical and clinical data. DNA microarray gene expression datasets have mainly gained significant attention to the research community owing to their ability to identify diseases through the “bio-markers” or specific alterations in the gene sequence that represent that particular disease (for example, different types of cancer). However, gene expression datasets are very high-dimensional, while only a few of those are “bio-markers”. Meta-heuristic-based feature selection effectively filters out only the relevant genes from a large set of attributes efficiently to reduce data storage and computation requirements. To this end, in this paper, we propose an Altruistic Whale Optimization Algorithm (AltWOA) for the feature selection problem in high-dimensional microarray data. AltWOA is an improvement on the basic Whale Optimization Algorithm. We embed the concept of altruism in the whale population to help efficient propagation of candidate solutions that can reach the global optima over the iterations. Evaluation of the proposed method on eight high dimensional microarray datasets reveals the superiority of AltWOA compared to popular and classical techniques in the literature on the same datasets both in terms of accuracy and the final number of features selected. The relevant codes for the proposed approach are available publicly at https://github.com/Rohit-Kundu/AltWOA. •DNA datasets have mainly gained significant attention to the research community.•They are very high-dimensional, while only a few of those are “bio-markers”.•To solve this problem, it is used the Altruistic Whale Optimization Algorithm.•It effectively filters out only the relevant genes from a large set of attributes.•Our method reveals its superiority compared to popular and classical techniques in the literature.